Role of foreign direct investment in economic growth of developing countries (Journal of Science-Innovative Research in Uzbekistan, 2024)
According to theory, foreign direct investment plays a significant role as a stimulant for industrial growth and helps with capital accumulation and technical advancement. We examine how foreign direct investment affects economic growth within the framework of an endogenous model which is an assumption that economic growth due to internal factors such improvements in innovation, knowledge to increased productivity, positively affecting the economic outlook. We test the claim that higher economic development nations benefit more from FDI inflows